The role of the veterinarian in improving the quality of life - L. Blajan (Hemera Zoa, 1988)
Quality of life is achieved through a variety of factors which, by combining to meet the various needs of man, create a state of well being.Since the beginning of time, animals have made a significant contribution to this state of well being, by providing man with food, industrial raw materials, energy and fertiliser. Moreover, in many societies they form an integral part of cultural life. Their socio-economic functions will necessarily become increasingly important in the modern world, confronted as it is by two structural phenomena : demographic growth and a shift of populations towards the towns.